Consumption, Solid Waste Generation and Water Pollutionin in Upper Mahaweli Catchment, Sri Lanka - Mahees, M.T.M.; Sivayoganathan, C.; Basnayake, B.F.A. (My University, 2011)
This sociological study focuses on the relationship of consumption patterns and solid waste generation and its impact on water pollution in the catchment of Pinga Oya, tributary of Mahaweli. This paper is based on the study of effects of socio-economic and political factors in solid waste generation and water pollution in River Mahaweli. The direct solid waste disposal into water bodies and the untreated dumping sites are supposed to be some of the major causes of water pollution in Sri Lanka. A comprehensive understanding of the causal link between consumption pattern and solid waste generation will bring about many underlining stories of waste disposal and its link with water pollution. Two hundred semi-structured household questionnaires and in-depth interviews with key informants were used to collect quantitative and qualitative data from Pinga Oya watershed areas. The samples were selected on stratified basis and data were analyased quantitatively and qualitatively. The secondary information was mostly collected from the sociological literature. The consumption patterns of people often determine the nature and amount of solid waste generation based on their livelihood, class and culture. Here, the symbolic consumption which has become the life style of urban middle and upper class people, promotes a “consumer society” with the influence of monthly household income and cultural ritual. As a result of higher social value given for mass consumption in this global economic order, people frequently consume unwanted goods to achieve symbolic value and cultural satisfaction rather than limiting their consumption to actual necessities. The consumption culture that generates more and more solid waste especially in urban social environment influence the quality of water and aggravates crisis of water pollution. Therefore, water pollution created by solid waste disposal is not just a problem limited to natural scientists to solve but it is a social problem caused by many socio- economic and cultural practices of people.
Keywords: Consumption; Solid Waste Generation